Estrogen receptor alpha: Molecular mechanisms and emerging insights. Issue 10 (16th August 2013) - Candelaria, Nicholes R.; Liu, Ka; Lin, Chin‐Yo
ABSTRACT Estrogen receptor alpha (ERα) is a cellular receptor for the female sex hormone estrogen and other natural and synthetic ligands and play critical roles in normal development and physiology and in the etiology and treatment of endocrine‐related diseases. ERα is a member of the nuclear receptor superfamily of transcription factors and regulates target gene expression in a ligand‐dependent manner. It has also been shown to interact with G‐protein coupled receptors and associated signaling molecules in the cytoplasm. Transcriptionally, ERα either binds DNA directly through conserved estrogen response element sequence motifs or indirectly by tethering to other interacting transcription factors and nucleate transcriptional regulatory complexes which include an array of co‐regulator proteins. Genome‐scale studies of ERα transcriptional activity and localization have revealed mechanistic complexity and insights including novel interactions with several transcription factors, including FOXA1, AP‐2g, GATA3, and RUNX1, which function as pioneering, collaborative, or tethering factors. The major challenge and exciting prospect moving forward is the comprehensive definition and integration of ERα complexes and mechanisms and their tissue‐specific roles in normal physiology and in human diseases. J. Cell. Biochem. 114: 2203–2208, 2013. © 2013 Wiley Periodicals, Inc.